Relevansi Mengkomunikasikan Doktrin Predestinasi Kepada Anak Sekolah Minggu Dalam Perspektif Teologi Reformed - Riawan Riawan; Aprianus L Moimau (LPPM - STT Kadesi Bogor, 2024)
of Reformed theology. This study highlights the importance of a sensitive and thoughtful approach to teaching complex concepts such as predestination through exploring theological understanding and considering children's developmental needs. Through an analysis of Reformed theology, this article highlights the importance of creating an educational environment that supports a balanced understanding of God's sovereignty and human responsibility. Therefore, this article provides practical guidance for religious educators to teach the doctrine of predestination to children in a Sunday School context appropriately and meaningfully.